2016
DOI: 10.1002/btpr.2344
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of pilot‐scale production of B‐phycoerythrin

Abstract: β-Phycoerythrin is a color protein with several applications, from food coloring to molecular labeling. Depending on the application, different purity is required, affecting production cost and price. Different production and purification strategies for B-phycoerythrin have been developed, the most studied are based on the production using Porphyridium cruentum and purified using chromatographic techniques or aqueous two-phase systems. The use of the latter can result in a less expensive and intensive recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Conventional equipment used by the chemical industry for organic-aqueous extraction, such as column contactors, has been mostly employed for large-scale and continuous ATPS applications (Cuhna and Aires-Barros, 2002 ). However, the study of alternative equipment configurations such as mixer settlers and the development of novel separators for different ATPS variants, bioproducts and physicochemical characteristics could increase the interest toward the industrial implementation of continuous ATPS-based processes (Cuhna and Aires-Barros, 2002 ; Benavides and Rito-Palomares, 2008 ; Torres-Acosta et al, 2016 ). Recently, Vázquez-Villegas et al ( 2011 ), proposed a novel mixer-settler device for continuous ATPS operation at bench scale.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional equipment used by the chemical industry for organic-aqueous extraction, such as column contactors, has been mostly employed for large-scale and continuous ATPS applications (Cuhna and Aires-Barros, 2002 ). However, the study of alternative equipment configurations such as mixer settlers and the development of novel separators for different ATPS variants, bioproducts and physicochemical characteristics could increase the interest toward the industrial implementation of continuous ATPS-based processes (Cuhna and Aires-Barros, 2002 ; Benavides and Rito-Palomares, 2008 ; Torres-Acosta et al, 2016 ). Recently, Vázquez-Villegas et al ( 2011 ), proposed a novel mixer-settler device for continuous ATPS operation at bench scale.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major constraints of large‐scale ATPS is the processing to remove phase components, which are considered contaminants. It was previously demonstrated that UF/DF can hinder the potential use of an industrial‐sized ATPS because the high turnover of membrane filters required for this unit operation, which contributes to high production costs . This needs to be evaluated, but the present work analyzed the increase in sample input, therefore requiring a reduced system which could become insensitive to the costs of phase removal operations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, modeling techniques, like Monte Carlo simulation, can be incorporated to mimic real‐life variation and understand their impact on production costs. Examples of successful application of these tools include comparisons between different types of equipment or operating strategies, optimization of different operation parameters, evaluation of different purification strategies, analysis of different strategies for developing autologous cell therapies, and analysis of pilot‐scale production of protein‐based pigments …”
Section: Introductionmentioning
confidence: 99%
“…112,113 An example of economic model analysis using BioSolve software was demonstrated for the production of royalacin, a protein found in royal jelly; 113 uricase -an enzyme responsible for breakdown of uric acid into allantoin; 114 and β-phycoerythrin -a color protein used as a food coloring agent. 115 The economics model analysis using experimental data, together with bioprocess simulation, will aid implementation of the bioprocess for fatty alcohol production or other bio-products at an industrial scale.…”
Section: Future Perspectives and Outlookmentioning
confidence: 99%